(untitled) (Vestígios - Revista Latino-Americana de Arqueologia Histórica, 2022)
BOLLWERK, Elizabeth A. & TUSHINGHAM, Shannon. Perspectives on the Archaeology of Pipes, Tobacco and other Smoke Plants in the Ancient Americas. USA: Springer International Publishing Switzerland, 2016, 267 p. ISBN 3319794981.